Understanding the tax compliance culture of private sector tax practitioners in South Africa - AKINBOADE, Oludele Akinloye (Journal of Economics and Behavioral Studies, 2014)
The paper presents the findings of a private sector tax practitioners segmentation survey conducted by South Africa Revenue Service to understand their tax compliance culture, appropriateness of SARS services to them and their client service needs. A set of structured questionnaires were administered to seven hundred and three tax practitioners in nine provinces which included open and closed questions. The level of tax compliance by the tax practitioner’s organization varies from province to province. Roughly, more than ninety percent of tax practitioners’ organizations that filed or submitted their organizations tax returns did so on time. Private sector tax practitioners are good e-filers. On average, assistance provided by SARS officials is considered to be very helpful. They prefer communication via email, internet, letters in the post, television and telephone calls. Most would like a dedicated SARS unit to serve them.